Anemia ‐ an initial manifestation of Bing‐Neel syndrome: A case report. Issue 46 (18th November 2022) - Yang, Xiaoqian; Chong, Zonglei; Ma, Congcong; Wang, Guifang; Yan, Chunxia
Abstract : Rationale: It is very likely that we will miss Bing-Neel syndrome (BNS) when its initial sign is anemia. Patient concerns: A 59-year-old woman presented with episodic loss of consciousness, anemia, and extremity muscle strength scores (5-) and extremity tendon reflexes (++). Diagnoses: Magnetic Resonance Imaging (MRI) showed abnormal signal in the left hippocampus, left insula, and right occipital lobe. Quantitative serum immunoglobulins showed elevated immunoglobulinm (IgM) (60.6g/L). Bone marrow biopsy showed lymphoplasmacytic lymphoma (LPL) and tested positive for the MYD88 L265P mutation suggesting Waldenström macroglobulinemia (WM). Interventions: The patient underwent 3 plasma exchange treatments in the department of hematology followed by chemotherapy (cyclophosphamide for injection, bortezomib for injection). Outcomes: The patient's condition improved after treatment. Lessons: Clinicians must remain vigilant, as BNS may be the only sign of WM progression in a patient well-controlled on treatment.